REPRESENTATION OF INDONESIAN’S BEAUTY CONCEPT IN “CITRA” HAND & BODY LOTION ADVERTISEMENT USING ROLAND BARTHES’ SEMIOTICS APPROACH - Kurniawan, Yulius; Putra, Yosua Ade; Fadilah, Eka (ELite Journal : International Journal of Education, Language and Literature, 2024)
This study explores the representation of beauty concept in Indonesian advertisements, with a focus on Citra's "Ragam Cantik Indonesia" advertisement, through the lens of Roland Barthes' semiotic theory. However, there is a gap in understanding how these beauty standards are constructed and communicated, particularly in the context of local brands like Citra. This research aims to fill this gap by analyzing the denotative, connotative, and myth to uncover the Indonesian beauty concept in Citra brand advertisement. The advertisement seeks to highlight the racial and cultural diversity of Indonesia,presenting a variety of beauty standards. It features models with diverse characteristics, including fair, brown, and dark skin tones, as well as straight, curly, and hijab-wearing hair styles. This selection clearly represents the multifaceted concept of beauty in Indonesia. Additionally, the ad aims to challenge the prevailing myth that ideal beauty is synonymous with having white skin.